Interactions Among Nerve Regeneration, Angiogenesis, and the Immune Response Immediately After Sciatic Nerve Crush Injury in Sprague-Dawley Rats - He, Bo; Pang, Vincent; Liu, Xiangxia; Xu, Shuqia; Zhang, Yi; Djuanda, David; Wu, Guanggeng; Xu, Yangbin; Zhu, Zhaowei (Frontiers in Cellular Neuroscience, 2021)
To preliminarily explore the primary changes in the expression of genes involved in peripheral nerve processes, namely, regeneration, angiogenesis, and the immune response, and to identify important molecular therapeutic targets, forty-five Sprague-Dawley (SD) rats were randomly divided into a control group and an injury group. In the injury group, tissue samples were collected at 4 days and 7 days after the injury for next-generation sequencing (NGS) analysis combined with gene ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis and Venn diagram construction to identify the differentially expressed mRNAs (DEmRNAs) associated with regeneration, angiogenesis, and the immune response of the nerve. The expression of genes in the distal and proximal ends of the injured nerve after injury was analysed by qRT-PCR. NGS revealed that compared with the control group, the injury group had 4020 DEmRNAs 4 days after injury and 3278 DEmRNAs 7 days after injury. A bioinformatics analysis showed that C-C chemokine receptor type 5 (CCR5), Thy1 cell surface antigen (Thy1), Notch homologue 1 (Notch1), and semaphorin 4A (Sema4A) were all associated with regeneration, angiogenesis, and the immune response of the nerve at both 4 days and 7 days after injury, but qPCR revealed no significant difference in the expression of Thy1 (P = 0.29) or Sema4A (P = 0.82) in the proximal end, whereas a significant difference was observed in CCR5 and Notch1 (P < 0.05). The trend in the Notch1 change was basically consistent with the RNA-seq result after injury, which implied its indispensable role during endothelial cell proliferation and migration, macrophage recruitment, and neurotrophic factor secretion.